Pelayanan Kesehatan Bagi Narapidana Lanjut Usia di Lembaga Pemasyarakatan Kelas IIA Yogyakarta - Adie Hendrawan, Richardus Batista; Butar Butar, Herry Fernandes (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the implementation of health services for the elderly (elderly) inmates in the penitentiary (Lapas) class IIA Yogyakarta. Using a qualitative approach with case study design, this study seeks to describe the available service models, identify constraining factors that hinder, and propose relevant improvement programs. Data collection was conducted through triangulation methods, namely in-depth interviews with key informants (prison Heads, health workers, and elderly inmates), participatory observation, and documentation analysis. The results indicate that although prisons have sought services, including through the SAMBALADA Program, the optimization has not been achieved. The main constraints include limited medical personnel, operating budgets, special facilities, and minimal attention to mental health aspects. Although elderly inmates showed a positive appreciation for routine services and drug availability, they raised the need for improved health education and medication monitoring. In response to these findings, this article proposes the "cheerful Twilight" Program as a holistic and sustainable approach to improving the quality of life of elderly inmates. Academically, this study contributes to enriching the literature on geriatric issues in the Indonesian correctional environment, as well as presenting empirical-based intervention models that can be a practical reference.